Control of nuclear receptor function by local chromatin structure - Wiench, Malgorzata (FEBS J, 2011)
Steroid hormone receptors regulate gene transcription in a highly tissue-specific manner. The local chromatin structure underlying promoters and hormone response elements is a major component involved in controlling these highly restricted expression patterns. Chromatin remodeling complexes, as well as histone and DNA modifying enzymes, are directed to gene-specific regions and create permissive or repressive chromatin environments. These structures further enable proper communication between transcription factors, co-regulators and basic transcription machinery. The regulatory elements active at target genes can be either constitutively accessible to receptors or subject to rapid receptor-dependent modification. The chromatin states responsible for these processes are in turn determined during development and differentiation. Thus access of regulatory factors to elements in chromatin provides a major level of cell selective regulation.